2014
DOI: 10.1002/maco.201307550
|View full text |Cite
|
Sign up to set email alerts
|

Dealloying of Al2Cu, Al7Cu2Fe, and Al2CuMg intermetallic phases to form nanoparticulate copper films

Abstract: International audienceCopper rich intermetallic particles are common in technical aluminum alloys. When exposed to an aggressive electrolyte, these particles undergo a transformation into a pure copper phase due to a selective dissolution or dealloying mechanism. In this work, the kinetics of this transformation have been investigated using synthetic intermetallic phases of Al2Cu, Al7Cu2Fe, and Al2CuMg in 2M H2SO4 as commonly used in the anodization process. The elementary dissolution rates for Al, Mg, Cu, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…This is due to the selective dissolution or dealloying of Al 7 Cu 2 Fe phase. A similar phenomenon has been reported in the work of Lebouil et al 37 For some large pits in the over-aged samples, the remnants of particles were not found because of the falling-out or dissolution of the remnants.…”
Section: Resultssupporting
confidence: 89%
“…This is due to the selective dissolution or dealloying of Al 7 Cu 2 Fe phase. A similar phenomenon has been reported in the work of Lebouil et al 37 For some large pits in the over-aged samples, the remnants of particles were not found because of the falling-out or dissolution of the remnants.…”
Section: Resultssupporting
confidence: 89%
“…Experimental studies also revealed the selective dissolution of Al from θ-Al 2 Cu, and suggested that crystallographic defects, such as stacking faults and dislocations, facilitate de-alloying of θ-Al 2 Cu. 13,41,42 The planar-extended and vertical-extended dislocation core could operate as precursor for de-alloying of θ-Al 2 Cu because of the increased local stored energy. Moreover, dislocation climb driven by their interaction will create a high population of vacancies.…”
Section: Discussionmentioning
confidence: 99%
“…1 The potential differences between the IMPs and the matrix may result in localized dissolution of the matrix or dealloying of the IMP. 2 The most common IMPs present in 2xxx and 7xxx series Al alloys include Al 2 CuMg (S-phase), Al 2 Cu (θ-phase), Al 7 Cu 2 Fe (β-phase), MgZn 2 (η-phase) and Mg 2 Si. [3][4][5] IMPs containing Cu and Fe, such as Al 2 Cu.…”
mentioning
confidence: 99%
“…6 and Al 7 Cu 2 Fe, 7 are considered to be cathodic with respect to the matrix, acting as local cathodes and thus promoting cathodic reactions such as oxygen reduction. In contrast, Mg-rich IMPs, such as Al 2 CuMg, are considered anodic relative to the matrix, resulting in selective dissolution and concomitant Cu-enrichment of the IMP. 8 These localized corrosion events may eventually trigger other corrosion forms, such as stress corrosion cracking or intergranular corrosion.…”
mentioning
confidence: 99%